2000
DOI: 10.1538/expanim.49.281
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Duodenal Brush Border Membrane and Specific Activities of Brush Border Membrane Enzymes in Wistar Rats.

Abstract: Abstract:To examine age-related changes in the morphology of intestinal brush border membrane (BBM; microvilli) and specific activities of intestinal BBM enzymes including alkaline phosphatase (ALP), γ-glutamyl transpeptidase (γ-GT), and disacchridase, four groups of Wistar rats were sacrificed at 2.5 wk, 5 wk, 5 mon and 23 mon. In an electron microscopic examination, morphologically a less dense BBM structure in the duodenum of rats aged 23 mon was observed than that of rats aged 5 mon. Specific activity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…Its activity increased markedly after fat feeding (13,17,20) and decreased after fasting, while refeeding elevated it to the pre-fasting level (26). AP in rodents is present at its highest level in the duodenum, and its activity decreases gradually toward the jejunum and ileum (10). The presented results show that besides the reduction of adiposity, consumption of a standard diet with citrus pectin also affected the small intestinal function, i.e., significantly decreased duodenal AP activity was found in 40-day-old pectin-fed rats in comparison with the pair-fed group.…”
Section: Discussionmentioning
confidence: 61%
“…Its activity increased markedly after fat feeding (13,17,20) and decreased after fasting, while refeeding elevated it to the pre-fasting level (26). AP in rodents is present at its highest level in the duodenum, and its activity decreases gradually toward the jejunum and ileum (10). The presented results show that besides the reduction of adiposity, consumption of a standard diet with citrus pectin also affected the small intestinal function, i.e., significantly decreased duodenal AP activity was found in 40-day-old pectin-fed rats in comparison with the pair-fed group.…”
Section: Discussionmentioning
confidence: 61%
“…Aging studies have shown a decrease in both the number and the length of epithelial microvilli and a declined function of plasma membrane enzymes and receptors (32)(33)(34)(35). Specifically, the decrease in the activity of some of the enzymes …”
Section: Discussionmentioning
confidence: 99%
“…Na ϩ /K ϩ -ATPase and Mg 2ϩ -ATPase were used for the basolateral and canalicular fractions of liver plasma membranes, respectively (Wolters et al, 1991). For the intestinal brush-border membranes alkaline phosphatase was used as a marker enzyme (Jang et al, 2000).…”
Section: Preparation Of Hepatic and Intestinal Membranes For Protein mentioning
confidence: 99%